Information Technology of Credit Collaterals That Will Be Auction Based on Google Maps - Prayudi, Satria; Mukhroji, Mukhroji; Ginting, Rossiana; Sufri, Rahmat; Danuasmo, Satrio (International Journal of Management Science and Information Technology, 2022)
Collateral is an asset owned by the borrower that is promised to the lender if the borrower is unable to repay the loan. If the borrower defaults, the lender can have the collateral at the beginning of the loan. The lack of dissemination of information, and the lack of informativeness of the media for delivering information on credit collateral that will be auctioned off to the general public has resulted in low competitiveness among buyers of collateral to be auctioned off. To solve this problem, an approach is needed in delivering information that is informative and on target. The purpose of this study is to increase prospective buyers, thereby triggering competitiveness against nominal bid prices, the process of delivering information to be more efficient and effective by implementing new innovations in advertising credit collateral information that will be auctioned. The methodology used in this paper is a Mind Map, flowmap and S.W.O.T analysis by developing a Geo-Location application for Credit Collateral that will be auctioned. By using this application, the company's revenue growth increases compared to not using the application.